Induction of targeted osteogenesis with 3-aryl-2H-benzopyrans and 3-aryl-3H-benzopyrans: Novel osteogenic agents. Issue 158 (April 2016) - Gupta, Atul; Ahmad, Imran; Kureel, Jyoti; Hasanain, Mohammad; Pandey, Praveen; Singh, Sarita; John, Aijaz A.; Sarkar, Jayanta; Singh, Divya
Graphical abstract: Highlights: 3-aryl- 2H -benzopyran and 3-aryl- 3H -benzopyran derivatives as novel osteogenic agents. 20b, 22a, 27 and32 showed significant osteogenic activity at EC50 values 1.35, 34.5, 407 and 29.5 pM. 20b and32 significantly increased mineral nodule formation and the transcript levels of BMP-2, RUNX-2 and osteocalcin at 100 pM. 22b showed anticancer activity at IC50 6.5–13.2 μM in human cancer cell lines, by inducing apoptosis and arresting cell cycle at sub-G0 phase. Abstract: Development of target oriented chemotherapeutics for treatment of chronic diseases have been considered as an important approach in drug development. Following this approach, in our efforts for exploration of new osteogenic leads, substituted 3-aryl- 2H -benzopyran and 3-aryl- 3H -benzopyran derivatives (19, 20a–e, 21, 22a–e, 26, 27, 28a–e, 29, 31a–b, 32 and33 ) have been characterized as estrogen receptor-β selective osteogenic (bone forming) agents. The synthesized compounds were evaluated for osteogenic activity using mouse calvarial osteoblast cells. Four compounds viz 20b, 22a, 27 and32 showed significant osteogenic activity at EC50 values 1.35, 34.5, 407 and 29.5 pM respectively. Out of these, 20b and32 were analyzed for their bone mineralization efficacy and osteogenic gene expression by qPCR. The results showed that20b and32 significantly increased mineral nodule formation and the transcript levels of BMP-2, RUNX-2 and osteocalcin at 100 pM concentrations respectively. Further mechanistic studies of20b and32 using transiently knocked down expression of ER-α and β in mouse osteoblast (MOBs) showed that20b and32 exerts osteogenic efficacy via activation of estrogen receptor-β preferentially. Additionally, compounds showed significant anticancer activity in a panel of cancer cell lines within the range of (IC50 ) 6.54–27.79 μM. The most active molecule, 22b inhibited proliferation of cells by inducing apoptosis and arresting cell cycle at sub-G0 phase with concomitant decrease in cells at S phase.